Pengaruh Gaya Kepemimpinan Transformasional dan Disiplin Kerja terhadap Kinerja Karyawan PT. Sumber Alfaria Trijaya Tbk. di Kota Makassar - Nur Wahida; Anwar Ramli; Chalid Imran Musa (International Forum of Researchers and Lecturers, 2024)
This study aims to determine whether there is an Effect of Transformational Leadership Style and Work Discipline on Employee Performance of PT Sumber Alfaria Trijaya Tbk. in Makassar City. To find out and analyze which variable is the dominant influence on employee performance at PT Sumber Alfaria Trijaya Tbk. In Makassar City. This type of research uses quantitative, the data analysis technique used in this research is multiple linear regression analysis using SPSS 22 for windows. That the significance value is 0.000 <0.05. That simultaneously leadership style and work discipline have a significant positive effect on employee performance. The results of this study are in accordance with the theory of Budi Setiyawan and Waridin (2006) that discipline is in an ideal state in supporting and carrying out tasks according to the rules in order to support work optimization. One of the conditions for discipline to grow in the work environment is the complete division of labor to the lowest employee or officer, so that people know consciously what their duties are, how to do it, when the work starts and finishes, as arranged in advance and understand who is responsible for the results of the work.